Differentiations in Illness Duration, Thyroid-Stimulating Hormone, Glucose and P300 Latency Between Drug-Naïve Unipolar and Bipolar Depression: A Comparative Cross-Sectional Study - Li C; Yang L; Zhang Q; Zhang Y; Li R; Jia F; Wang L; Ma X; Yao K; Tian H; Liu Z; Zhuo C (Neuropsychiatric Disease and Treatment)
Chao Li,1,2 Lei Yang,1,2 Qiuyu Zhang,1,2 Ying Zhang,1,2 Ranli Li,1,2 Feng Jia,1,2 Lina Wang,1,2 Xiaoyan Ma,1,2 Kaifang Yao,1,2 Hongjun Tian,3,* Zengxun Liu,4,* Chuanjun Zhuo1,2,* 1Computational Biology and Animal Imaging Center (CBAC), Tianjin Anding Hospital, Nankai University Affiliated Tianjin Anding Hospital, Tianjin Medical University Affiliated Tianjin Anding Hospital, Tianjin Medical University Affiliated Tianjin Mental Health Center, Tianjin, 300222, People’s Republic of China; 2Laboratory of Psychiatric-Neuroimaging-Genetic and Co-morbidity (PNGC_Lab), Tianjin Anding Hospital, Tianjin Mental Health Center of Tianjin Medical University, Tianjin, 300222, People’s Republic of China; 3Department of Psychiatry, Tianjin Fourth Center Hospital, Nankai University Affiliated Tianjin Fourth Center Hospital, Tianjin, 300140, People’s Republic of China; 4Department of Psychiatry, Shandong Mental Health Center, Jinan, 250014, People’s Republic of China*These authors contributed equally to this workCorrespondence: Chuanjun Zhuo, Tianjin Anding Hospital, Nankai University Affiliated Tianjin Anding Hospital, Tianjin Medical University Affiliated Tianjin Anding Hospital, Tianjin Medical University Affiliated Tianjin Mental Health Center, Tianjin, 300222, People’s Republic of China, Tel/Fax +86-22-24394542, Email chuanjunzhuotjmh@163.comBackground: Distinguishing bipolar depression (BD) from unipolar depression (UD) remains a major clinical challenge, especially in drug-naïve patients. The present study aimed to investigate whether demographic, clinical, and biochemical parameters can help differentiate drug-naïve BD from UD.Methods: Drug-naïve patients with UD and BD were recruited from Shandong Mental Health Center. Ninety-four inpatients (61 UD and 33 BD) were assessed using the 17-item Hamilton Depression Rating Scale (HAMD-17) and P300 latency. Fasting serum levels of free triiodothyronine (FT3), free thyroxine (FT4), thyroid-stimulating hormone (TSH), as well as fasting plasma glucose (FPG), lipid, C-reactive protein (CRP), and uric acid (UA) indicators were measured.Results: Patients with BD had longer illness duration and P300 latency and lower FT3 levels, but higher levels of TSH and FPG than patients with UD (all P< 0.05). Binary logistic regression analysis indicated illness duration, TSH, FPG, and P300 latency were significantly associated with BD. Illness duration, TSH, FPG, and P300 latency achieved an area under the ROC curve of 0.777, 0.699, 0.646, and 0.635, respectively, in discriminating unipolar and bipolar depression.Conclusion: Increased illness duration, serum TSH and FPG levels, and P300 latency were independent risk factors for BD. Demographic, clinical, biochemical, and electrophysiological markers identified may have the potential to distinguish BD from UD.Keywords: unipolar depression, bipolar depression, illness duration, thyroid-stimulating hormone, fasting plasma glucose, P300